Participation and social control: the case of the ConCidade in Londrina/PR (PerCursos, 2023)
Since the end of the 1980s, Brazilian urban policy has seen an equitable insertion of popular segments into various channels of popular participation. In addition to the Federal Constitution of 1988 and the City Statute of 2001, the creation of the Ministry of the Cities (2003) and of various councils, including the Council of the Cities (Conselho das Cidades - ConCidade) in 2004, which became part of the structure of the Ministry of the Cities, were also important in this process of fostering and enforcing participation in urban public policies during the 2000s. Thus, based on this context and on the city of Londrina located in the North of Paraná, the objective is to analyze the representativeness of the social participation as a constitutive and constituent element of the democratic process of construction of social rights. Since this is a research of qualitative approach, the interpretation of reality occurred through dialectical materialism, a method capable of covering the totality and presenting reality as a synthesis of multiple determinations, starting from the materiality of the real, the existing empirical world. It was verified during the research that, as of 2012, there was a deadlock in the implementation of the ConCidade at the municipal level, motivated by the conflict of interests between agents that produce the urban space and popular segments. In this dispute occurred the weakening of popular groups and the interruption of the creation of a city council with legitimate popular participation. With the approval of the revision of the Master Plan, the municipality has a new participatory instance since 2022 through the Municipal Council for Planning and Territorial Management.
Keywords: social participation; social control; right to the city